2017
DOI: 10.7577/radopen.2000
|View full text |Cite
|
Sign up to set email alerts
|

Radiation knowledge among radiographers and radiography students

Abstract: ObjectiveTo evaluate the knowledge of radiation among radiographers and radiography students in Nepal Methods A validated questionnaire was conducted among radiographers and radiography students in 24 th annual meeting and workshop of Nepal Radiological Society (NRS) on 10 th September, 2015. The survey included multiple choice questions (MCQs) related to demographic characteristics (age, gender), academic qualification, work experience and knowledge of radiation. The data were analyzed using SPSS software ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This is a paramount study that highlight the awareness of radiation protection in a private institution in Nepal. Previously, Maharjan has also carried out similar study and resulted adequate knowledge among radiographers and radiography students participated in an annual conference of Nepal Radiological Society (NRS) [20]. Jha et al also concluded average knowledge, poor perception and satisfactory practices of radiation risk among technical and non-technical staff of radiology department and stressed the malpractice of x-radiation imaging [23].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is a paramount study that highlight the awareness of radiation protection in a private institution in Nepal. Previously, Maharjan has also carried out similar study and resulted adequate knowledge among radiographers and radiography students participated in an annual conference of Nepal Radiological Society (NRS) [20]. Jha et al also concluded average knowledge, poor perception and satisfactory practices of radiation risk among technical and non-technical staff of radiology department and stressed the malpractice of x-radiation imaging [23].…”
Section: Discussionmentioning
confidence: 87%
“…This is a paramount study that highlight the awareness of radiation protection in a private institution in Nepal. Previously, Maharjan has also carried out similar study and resulted adequate knowledge among radiographers and radiography students participated in an annual conference of Nepal Radiological Society (NRS) [ 20 ]. Jha et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instruments presented in earlier studies assessed awareness, understanding and attitudes regarding ionising radiation and protection individually, but not together [20][21][22] . Previous studies that have presented instruments for measuring radiation protection have been limited to measuring variables categorically or the authors did not provide any information on the validation of the instrument or measured radiographers' and radiography students' awareness of radiation protection but was not applicable for measuring other healthcare professionals' knowledge of radiation safety [20][21][22] . The instrument presented in this study measures healthcare professionals' knowledge in three different areas of radiation, namely, physics and radiation biology, regulation concerning radiation protection, and radiation use in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest evidence, healthcare professionals do not have sufficient skills to effectively communicate benefit-risk information about paediatric imaging examinations [18][19] . The knowledge, skills and attitudes on radiation protection of healthcare professionals have been measured in multiple studies, all of which applied their own instruments [8][9][10]17,[20][21][22] . Dianati et al (2014) validated a questionnaire and checklist measuring radiation protection knowledge and behaviours by conducting a study with nurses.…”
Section: Introductionmentioning
confidence: 99%